The Quantitative Measurement of ST-Segment Deviation and Pathological Q Wave for Predicting Hospitalization Mortality in Patient with ST-Elevation Myocardial Infarction - Muhammad Surya Tiyantara; Yustye Yustye; Djoen Herdianto; Swandari Paramita (The Indonesian Heart Association, 2019)
Background: The appearance of ST-segment elevation (STE) and pathological Q wave were signs of worse myocardial damage and function, the quantitative measurement of the waves have a potential prognosis role. This study assesses the performance of the quantitative measurement of the waves in predicting in-hospital mortality and compares it with the Global Registry of Acute Coronary Events (GRACE) score as the standard recommended risk score. Methods: This was a cross-sectional study included patients with ST-elevation myocardial infarction (STEMI) that hospitalized in Abdul Wahab Sjahranie General Hospital Samarinda during January to December 2016. Standard 12-lead electrocardiograms (ECG) were assessed at patient admission as well as other data for GRACE score. The subjects were grouped into non-survivor and survivor group based on hospitalization survival state, and six quantitative ECG characteristics performance will be assessed. The performances were assessed using receiver operating characteristics (ROC) curve and area under the curve (AUC). Results: There were 57 subjects consisting of 9 non-survivor subjects. The AUC of the four ECG characteristics highest STE amplitude, deepest Q amplitude, total Q amplitude, and total STE amplitude did not significantly different with GRACE score (p>0.05). Highest STE amplitude has the best performance than the other ECG characteristics (AUC=0.81, 95% CI:0.65 to 0.97), and cut off point 4.5mm provides 56% sensitivity and 94% specificity. Conclusion: The quantitative measurement of ST-segment deviation and pathological Q wave have the prognosis role for predicting in-hospital mortality.